An experimental and numerical study of softball to facemask impacts - Schwizer, P.; Demierre, M.; Smith, L. V. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
Concussion awareness in sports-related injuries has increased over the past decade. This awareness has resulted in improvement in protective equipment and in our understanding of head injury. While contact sports such as ice hockey and football have been at the forefront of the discussions surrounding concussion, concussion also occurs in non-contact sports like softball and baseball. The aim of this project was to describe facemask response to ball impacts. The study involved one facemask design and two types of foam paddings. A method is presented that allows foam characterization at deformation rates and magnitudes representative of play conditions. The facemask/foam system was placed on a Hybrid III headform and impacted with softballs to measure its response experimentally. A numerical model of the facemask/foam system on a Hybrid III headform showed good agreement with experimental data. Facemask impacts with a stiffer foam showed superior attenuation at high speeds (above 30?m/s) while a softer foam attenuated impacts better at low speeds.